Reducción del tiempo de entrega de pedidos utilizando Kanban, TPM y 5s en una fábrica textil peruana. Una revisión empírica - Jarufe Majluf, Francesca Maria (2023)
The importance of reducing delivery times is vital for customer loyalty and the reduction of losses due to cancellation of orders, this being the problem that was developed in the investigation. After recollecting the data, it was observed that the main causes of delays are in the production area, so, using the 5S, Kanban and TPM tools, it was possible to attack the different problems that were found in the company under study. and thus productivity and efficiency were improved, validating the results in the Arena simulation software, not only was it concluded that the different tools used were able to mitigate the eventualities of the current state of the factory, but also proceeded to simulate 3 parallel different scenarios that could occur in the company, obtaining results similar to our first simulation, thus validating that these improvements not only apply to the current state of the company but also to possible future scenarios.